2022
DOI: 10.1093/ajcn/nqac035
|View full text |Cite
|
Sign up to set email alerts
|

Orally consumed ginger and human health: an umbrella review

Abstract: Background Emerging evidence supports the health benefits of ginger for a range of conditions and symptoms; however, there is a lack of synthesis of literature to determine which health indications are supported by quality evidence. Objectives This umbrella review of systematic reviews aimed to determine the therapeutic effects and safety of any type of ginger from the Zingiber family administered in oral form compared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 53 publications
0
34
1
1
Order By: Relevance
“…De manera similar la combinación de jengibre, cúrcuma y pimienta negra revelan revelan que cuya ingesta dos veces al día durante 4 semanas mejoran los niveles de PGE2 en pacientes con osteoartritis crónica de rodilla similar al fármaco naproxeno (64), sin embargo, no hay pruebas suficientes para el uso de jengibre oral con finalidad de alivio del dolor y mejora de función en OA de rodilla, pero tiene un efecto antiemético y control glucémico en embarazadas (65,66).…”
Section: Tablaunclassified
“…De manera similar la combinación de jengibre, cúrcuma y pimienta negra revelan revelan que cuya ingesta dos veces al día durante 4 semanas mejoran los niveles de PGE2 en pacientes con osteoartritis crónica de rodilla similar al fármaco naproxeno (64), sin embargo, no hay pruebas suficientes para el uso de jengibre oral con finalidad de alivio del dolor y mejora de función en OA de rodilla, pero tiene un efecto antiemético y control glucémico en embarazadas (65,66).…”
Section: Tablaunclassified
“…Although the therapeutic effects and safety of ginger have been investigated in many clinical trials, in other conditions, including pregnancy-, postoperative- or chemotherapy-related nausea and vomiting, metabolic syndrome, colorectal cancer, irritable bowel syndrome, osteoarthritis, rheumatoid arthritis, and primary dysmenorrhea, clinical evidence in PD is still lacking. , In the broader field of neurodegenerative disorders, two randomized double-blind placebo-controlled clinical trials in patients with cognitive impairment have demonstrated that oral ginger administration for three months was associated with improved scores on neuropsychological testing. , No severe side effects were mentioned in these two studies, and these promising results open the way for future clinical trials in patients with PD. The absence of clinical evidence on the therapeutic efficacy and safety of ginger in patients with PD is an important limitation for its clinical translation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Most common side effects of ginger in human studies are mild gastrointestinal symptoms including heartburn or reflux, nausea, diarrhea, and abdominal discomfort, regardless of the type of study population. 23,24 Other less common side effects are rash, flushing, and bad taste. 23 Reduction of aggregation of platelets and anticoagulant activity may be observed at high doses (10 g of ginger powder/daily), but no effects on platelet activity have been noted at doses of less than 4 g/day.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations